Analysis Of Regional Leading Sector DKI Jakarta Province Using Klassen Typology and Location Quotient (LQ) in 2017-2019 - Vebrina Hania Cholily; Yanuar Wendy Wardana (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to determine the pattern and structure of economic growth and the leading sectors of each Regency/City in DKI Jakarta Province. The data used is secondary data from 2017 – 2019. The analysis technique used is Klassen Typology and Location Quotient (LQ). The results showed that five cities in DKI Jakarta were categorised as regions with high levels of income and growth, while Seribu Island was categorised as low. For LQ analysis, three regions dominate in the agriculture, forestry, and fisheries sectors and for other regions, they dominate in other sectors.